1995
DOI: 10.1111/j.1528-1157.1995.tb01061.x
|View full text |Cite
|
Sign up to set email alerts
|

Sudden Death in Epilepsy: A Study of Incidence in a Young Cohort with Epilepsy and Learning Difficulty

Abstract: Sudden death, often seizure related, may occur in patients with epilepsy. Population-based incidence is probably on the order of 1:1,000/year. The incidence is much higher in selected groups, however. We wished to establish the incidence of sudden unexpected death (SUD) in a young cohort with severe epilepsy and learning difficulties. The study cohort included 310 pupils with epilepsy enrolled at a special residential school between April 1970 and April 1993. The follow-up period totaling 4,135 person-years in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
157
2
10

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 291 publications
(176 citation statements)
references
References 28 publications
6
157
2
10
Order By: Relevance
“…W większo-ści przypadków dochodzi do tego w nocy lub podczas snu, bez świadków zdarzenia [650]. Największym czynnikiem ryzyka SUDEP są częste drgawki, a zwłaszcza uogólnione drgawki toniczno-kloniczne [651][652][653][654][655][656][657][658][659][660].…”
Section: Nagły Niewyjaśniony Zgon W Przebiegu Padaczkiunclassified
“…W większo-ści przypadków dochodzi do tego w nocy lub podczas snu, bez świadków zdarzenia [650]. Największym czynnikiem ryzyka SUDEP są częste drgawki, a zwłaszcza uogólnione drgawki toniczno-kloniczne [651][652][653][654][655][656][657][658][659][660].…”
Section: Nagły Niewyjaśniony Zgon W Przebiegu Padaczkiunclassified
“…20,23 In cohorts of epilepsy patients with learning difficulties, SMRs were between 5.0 and 15.9. 24,25 Ten of the 29 patients who died in our cohort had associated physical and/or mental handicap.…”
Section: Mortality Ratesmentioning
confidence: 99%
“…Most studies reported that only 10% of deaths were witnessed, usually in association with GTCS [13,14]. Another study on SUDEP among patients with learning disabilities found that all 14 deaths occurred while the patients were unsupervised and unobserved [20]. Some of the early studies on SUDEP reported that around 50% of patients were found dead in bed and the majority were in the prone position [21,22].…”
Section: Risk Factorsmentioning
confidence: 99%